Managerial Strategies to Accelerate Lead Times with the Failure Mode and Effect Analysis (FMEA) Method (Qualitative Study at Naibonat Regional General Hospital, Kupang Regency) - Samlek Elisawyn Sunbanu; Erliany Syaodih; Dadang Kusnadi (CV. Civiliza Publishing, 2026)
This study aims to formulate a managerial strategy to accelerate waiting time through the identification of the root of the problem using the Failure Mode and Effect Analysis (FMEA) method. The research used a qualitative design involving five groups of informants, namely patients, specialist doctors, nurse at output patient clinics, medical record officers and management. Data were collected through in-depth interviews, observations, and Likert scale assessments, then analyzed using the FMEA approach to determine the Severity, Occurrence, Detection, and Risk Priority Number (RPN) values in each failure mode. The results of the study showed four failure modes with the highest RPN scores, namely: Hospital Management Information System failure (RPN 47.75), registration administration process (RPN 43.40), repeated service failures (RPN 42.05), and delay in specialist doctor attendance (RPN 40.98). HMIS is the most critical factor because it has the highest frequency of disruptions and has a direct impact on the entire service flow. Other dominant obstacles are delays in medical record files, insynchronization of administrative processes, and obstacles in pharmaceuticals. Based on these findings, the proposed managerial strategies include short-term improvements (optimization of human resources and SOPs), medium-term (digitalization through EMR and e-prescribing), and long-term (strengthening of Hospital Management Information System infrastructure and implementation of CQI). This research confirms that accelerating waiting times requires an integrated managerial approach, focusing on digitalization and cross-unit coordination.